PENGARUH LEADERSHIP TRANSFORMATIONAL PENDIDIKAN DAN PELATIHAN SERTA KOMITMEN ORGANISASIONAL TERHADAP KINERJA DAN LOYALITAS SEBAGAI VARIABEL INTERVENING (STUDI PADA RUTAN KELAS IIB SITUBONDO) - Kristiawan, Rudi (Relawan Jurnal Indonesia, 2023)
The aim of the research is to obtain empirical evindence of the effect of transformational leadership in education and training and organizational commitment on performance and loyalty as intervenning variables. By using the Partial Least Square (PLS) quantitative approach. Empirical finding obtaind that transformational leadership has a significant positive effect on loyalty, education and traoining has a significant positive effect on loyalty, organizational commitment has a significant positive effect on loyalty, tranformational leadersip has a positive but not significant effect on performance, education and training has a significant positive effect on performance commitment organizational has a significant positive effect on performance. Loyalty has a significant positive effect on performance, transformational leadership has a significant positive effectr on performance through loyalty, and education and training has a significant positive effect on performance through organizationalcommitment has a significant positive effect on performance through loyalty.